The Analysis of Question Item on Tarikh Subject with Rasch Model Theory - Subando, Joko; Saleh, Minhayati; Ngatimin, Ngatimin (Universitas Negeri Semarang, 2022)
This research has a purpose to find out the level of students' ability to work on the questions, the suitability of the individuals with the items, the level of difficulty of the items, the suitability of the items, and the interaction of individuals with the items by using the Rasch model theory. The data collection technique is with documentation, the data collected is in the form of answers from VII grader students of Madrasah Quraniyah Karanganyar taken from the end of the odd semester exam for the 2021/2022 school year. The number of respondents is 23 students and the number of questions is 25 items. The data are analyzed by using the Rasch model theory with the help of the Winstep program. The research result shows that (1) there are 2 students with high abilities (ex11, ex19) and 3 students with low abilities (ex3, ex9, ex12); (2) students who do not fit the model or have misconceptions about the questions are ex16, ex12, ex22, ex09, ex15, and ex21; (3) the most difficult questions are considered to be 2 items (B12, B29), the others are categorized as a medium; (4) the items that do not fit the model are B12, B20 and B24. Research finding generally shows that the test takers' abilities are above the item difficulty level, so the questions must be improved further.